Предмет: Алгебра, автор: Аноним

 √12-2√27+75= решите пожалуйста 3√2(5√2-√32)             решите(4-5√2)в квадрате        (√7-2√3)(√7+2√3)=

Ответы

Автор ответа: aproo
0

√12-2√27+75=√4*3-2√3*9+75=2√3-6√3+75=75-4√3

3√2(5√2-√32)=30-3√32*2=30-3√64=30-24=6

(√7-2√3)(√7+2√3)=7+2√3*7-2√3*7-12=7-12=-5

(4-5√2)^2=4^2-2*4*5√2+(-5√2)^2=16-40√2+50=66-40√2

Автор ответа: Svet1ana
0

sqrt{12}-2sqrt{27}+75=sqrt{4cdot3}-2sqrt{9cdot3}+75=2sqrt{3}-6sqrt{3}+75=75-4sqrt{3}

====================================================================3sqrt{2}(5sqrt{2}-sqrt{32})=sqrt{18}(sqrt{50}-sqrt{32})=sqrt{18cdot50}-sqrt{18cdot32}=sqrt{900}-sqrt{576}=30-24=6

====================================================================

(4-5sqrt{2})^{2}=4^{2}-2cdot4cdot5sqrt{2}+(-5sqrt{2})^{2}=16-40sqrt{2}+(-sqrt{25cdot2})^{2}=16-40sqrt{2}+(-sqrt{50})^{2}=16-40sqrt{2}+50=66-40sqrt{2}

====================================================================

(sqrt{7}-2sqrt{3})(sqrt{7}+2sqrt{3})=sqrt{7}cdotsqrt{7}-2sqrt{3}cdot2sqrt{3}=(sqrt{7})^{2}-(2sqrt{3})^{2}=(sqrt{7})^{2}-(sqrt{12})^{2}=7-12=-5

Похожие вопросы